A Foresight Study on Adoption of Autonomous Long-Haul Trucks among Logistics Industry in Malaysia - Lim Wen Ru,; Nor Kamariah Kamaruddin, (Research in Management of Technology and Business, 2024)
Autonomous long-haul trucks (ATs), one of the most cutting-edge technologies available today, significantly contributed to the development of logistics companies. In the coming years, the advent of autonomous long-haul trucks is poised to revolutionize the logistics and transportation industry, presenting a monumental game-changer with far-reaching implications. However, research on the adoption of Autonomous Long-Haul Trucks among logistics companies in Malaysia is limited. Hence, this study seeks to analyze the primary factors driving the Autonomous Long-Haul Trucks and to study the future image of their adoption within logistics companies in Malaysia. In this study, both qualitative and quantitative methods are used. STEEPV analysis applied as a foresight methodology. A questionnaire was used to identify the primary issues and drivers, as well as the impact-uncertainty analysis that corresponds to the adoption of autonomous long-haul trucks technology in the future. Among 275 distributed questionnaires to employees in Malaysian logistics companies, only 63 responded, resulting in a 38.89% response rate. The study identified legal and regulatory framework and technological advancements as the top two key drivers, showing the highest impact and uncertainty. Based on the findings of the study, four scenarios emerged were revolutionized transportation innovation, reduced efficiency, slow technological adoption, and safety and security risks.